The Convergence of AI and Health: Best Wearable Devices for Continuous Monitoring - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The Convergence of AI and Health: Best Wearable Devices for Continuous Monitoring The landscape of personal health management is undergoing a profound t...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care